Історія відкриття пам’яток давнього кам’яного віку Ізюмщини - Сніжко, І.А. (My University, 2011)
Снежко И. А. История открытия памятников древнего каменного века Изюмщины Все памятники древнего каменного века, известные на сегодняшний день на территории Харьковской области, концентрируются в среднем течении р. Северский Донец, на участе от г. Изюм до с. Яремовка. Их открытие связано с деятельностью Н. В. Сибилева в 1920–1940 гг., И. Ф. Левицкого в 1950 г. и работами экспедиции Харьковского исторического музея в 1988–2010 гг. Н. В. Сибилев более чем за два десятилетия досконально изучил этот район, открыв здесь 7 местонахождений, связанных с поздним палеолитом. И. Ф. Левицкий в ходе разведки, проведенной совместно с Д. Я. Телегиным, посетил окрестности сел Синичино и Каменка и сделал несколько зачисток. Автором публикации полностью раскопан один памятник, работы на втором продолжаются, несколько пунктов отмечено в ходе разведок. Возникает вопрос — это новые памятники или те, что были открыты нашими предшественниками? Его решению посвящена данная статья. I. Snizhko. The History of Discovering sites of the early stone Age in the Izyum Region All the sites of the early Stone Age in Kharkiv region known today are concentrated in the middle course of the Seversky Donets river in the area about Izyum town and Yaremovka village. Their discovery is connected with activity of N. V. Sibilyov in 1920–1940 and I. F . Levitsky in 1950, as well as the work of the Kharkiv History Museum in 1988–2010. N. V. Sibilyov has thoroughly studied this region for more than two decades, having discovered seven areas relating to the late paleolith. During the exploration I. F. Levitsky jointly with D. Y. Telyagin has visited the outskirts of the villages Sinitchino and Kamenka; there he has made several rabotages. The author of the publication has completely investigated one site, the second is still being investigated, some places were noticed during the explorations. A question arises — are these sites new or were they discovered by our predecessors? This article deals with this question.
Keywords: поздний палеолит; среднее течение р. Северский Донец; Н. В. Сибилев; И. Ф. Левицкий; late paleolith; middle course of the Seversky Donets; N. V. Sibilyov; I. F. Levitsky